ESG-Based Islamic Finance: Opportunities and Challenges in Building the Sustainability of Islamic Economics Amid Issues of Usury and Corruption - Said, Muhammad; Ahmad, Ahmad; SR, Naharuddin (Al-Infaq: Jurnal Ekonomi Islam, 2025)
This study explores the opportunities and challenges of integrating Environmental, Social, and Governance (ESG) principles into Islamic finance to strengthen the sustainability of the Islamic economic system amid the issues of usury (riba) and corruption. Using a systematic literature review (SLR) approach covering studies from 2020 to 2025, the findings show that ESG is aligned with Maqasid al-Shariah and has the potential to reinforce non-exploitative Islamic financial instruments such as green sukuk, profit-sharing contracts, zakat, and productive waqf. Opportunities are evident in enhancing financial stability and social inclusion, as demonstrated by the global ESG sukuk market growth and the success of hybrid ESG-Shariah models in the UAE. However, challenges remain in the form of regulatory misalignment, high compliance costs, and corruption practices that reduce investor trust and increase risks of greenwashing. The study highlights strategies such as adopting the IFSB hybrid ESG-Shariah framework, leveraging blockchain for transparent fund tracking, harmonizing regulations, and strengthening the role of Shariah Supervisory Boards (SSB). Overall, this research contributes both theoretically and practically by offering a conceptual model and policy recommendations to foster a sustainable Islamic economy free from riba and corruption while advancing the Sustainable Development Goals (SDGs).